Моніторинг гідрографічних об’єктів засобами дистанційного зондування Землі та геоінформаційних технологій - Третяк, Софія Корнилівна (Національний університет "Львівська політехніка", 2019)
В дисертаційній роботі подано методику дослідження зміщень русел річки Дністер та її правобережних і лівобережних приток на підставі топографічних карт, космічних зображень та спеціальних карт з опрацюванням всіх матеріалів в програмному середовищі ArcGIS. Розглянуто суть руслових процесів та методи їх дослідження. Проаналізовано вплив геологічних структур на зміщення русла річки Дністер та його приток від витоків річки до м. Заліщики, де річка Дністер протікає в каньйоні. На основі спрощених формул Молоденського визначено вплив похибок параметрів на точність трансформації при переході від однієї системи координат до іншої. Пораховано коефіцієнти стійкості русел та встановлено, що деякі вирази не відповідають визначеними авторами критеріям стійкості. Запропоновано вираз для визначення стійкості, в який входить ширина заплави та ширина русла річки. В диссертационной работе представлено методику исследования смещений русел реки Днестр и ее правобережных и левобережных притоков по топографическим картам, космическим изображениям и специальным картам с обработкой всех материалов при использовании програмного комплекса ArcGIS. Проанализировано влияние геологических структур на смещение русла реки Днестр и его приток. На основе упрощенных формул Молоденского определено влияние погрешностей параметров на точность трансформации при переходе от одной системы координат к другой. River channel monitoring and determination of the characteristics of river channels are performed for the purpose of solving specific tasks of hydraulic engineering, designing power lines, gas pipes, and pipelines when crossing rivers, defining the boundaries of protected lands in the land registry, taking into account deformations of river channels in recreational activities and in environmental disturbance assessment. Modern technologies for obtaining and processing information using data from Earth remote sensing and geoinformation systems opened up new possibilities for solving these tasks. In the first chapter, the essence of river channel processes and methods used for their study, as well as the main morphometric characteristics and methods of determining stability and sinuosity of river channels, are considered. The analysis of literary sources includes both theoretical approaches and experimental works related to river channel processes, in particular to the methods of studying river channel shifts, factors influencing them, and their importance for solving particular tasks of environmental management. The second chapter contains a technological scheme of the method which was used for determining horizontal shifts of the Dniester river channels according to topographic maps of different periods, space images, and maps of quaternary sediments, as well as soil maps, with further processing of materials in the ArcGIS software environment, which provides an opportunity to analyze shifts and obtain their metric values. The influence of geological structures on shifts of the Dniester river channels and its tributaries, from the riverhead to the town of Zalishchyky, where the Dniester river flows through a canyon, was analyzed. Since part of the Dniester river and its right-bank tributaries flow within the Precarpathian Trough, while the rest of the Dniester river and its left-bank tributaries flow within the Volyn-Podilia platform, such a change in geological structures has a dominant impact on the nature of rivers. Based on the simplified Molodensky transformations, the influence of errors in the transition parameters on the accuracy of transformation when switching from one coordinate system to another was determined. This method allows one to determine the accuracy of the transformation of historical maps into modern topographic maps. It was found that some expressions do not meet stability criteria determined by the authors. An expression which can be used for determining stability was suggested, which includes floodplain width and river channel width. This chapter also deals with the use of UAVs when building digital elevation models for hydrological modeling and its use under the conditions of complex river channel configuration and significant river meandering. The nature of streams of right-bank and left-bank tributaries are analyzed in the third chapter, horizontal river channel shifts of these rivers are also determined. The main difference in the nature of the right-bank and left-bank tributaries of the Dniester River, in our opinion, lies in the impact of geological structures. Stability and sinuosity coefficients were analyzed using different mathematical expressions. Design organizations, agencies, and municipal structures in which the results of the study can be used were indicated.
Мониторинг гидрографических объектов средствами дистанционного зондирования Земли и геоинформационных технологий
Monitoring of hydrographic objects using means of Earth remote sensing and geoinformation technologies
Keywords: моніторинг; руслові процеси; зміщення русла; річка Дністер; топографічні карти; космічні зображення; карти четвертинних відкладів; карти грунтів; алювіальні та делювіальні відклади; геологічна структура; повені; багаторукавність; мониторинг; русловые процессы; смещение русла; река Днестр; топографические карты; космические изображения; карты четвертичных отложений; карты почв; аллювиальные и делювиальные отложения; геологическая структура; наводнения; многорукавность; monitoring; river channel processes; channel displacement; Dniester river; topographic maps; space images; maps of quaternary sediments; soil maps; alluvial and diluvial deposits; geological structure; floods; large number of river branches; 528.92